Herpetofauna diversity and distribution based on the elevational range in West Java, Indonesia - Tatang Suharmana Erawan; Jirjiz Jauhan; Teguh Husodo; Indri Wulandari; Deri Achmad Fauzi; Erri Noviar Megantara; Sya Sya Shanida (Society for Indonesian Biodiversity, 2021)
Abstract. Erawan TS, Jauhan J, Husodo T, Wulandari I, Fauzi DA, Megantara EN, Shanida SS. 2021. Herpetofauna diversity and distribution based on the elevational range in West Java, Indonesia. Biodiversitas 22: 4308-4319. The herpetofauna discovery in West Java is still low and has not yet described the herpetofauna community's species diversity entirely and thoroughly in West Java. It experiences high anthropogenic impacts both from infrastructure and tourism activities. If left further, herpetofauna species will become extinct locally because of anthropogenic factors. Therefore, it is essential to reveal the diversity and distribution of herpetofauna species. This study aimed to show diversity and distribution based on the elevational range in West Java. Visual Encounter Survey in combination with the Auditory Encounter Survey was applied in this study. We found 74 species where the Colubridae family were found most commonly in the study sites. Of 74 species, four species have high conservation status, including Rhacophorus reinwardtii, Ophiophagus hannah, Varanus salvator, and Malayopython reticulatus. Besides, ten species were found to be endemic to Java and Java-Bali. Based on elevation, herpetofauna is mainly located at elevations < 1000 m asl. The higher the height, the fewer the number of species found. In Amphibians, the highest number of species tend to be found at 400-1200 m asl and 1400-1700 m asl, while reptiles tend to be located at 400-900 m asl. Keywords: Auditory Encounter Survey, West Java